Molecular Aspects of Plant Salinity Stress and Tolerance - Chen, Jen-Tsung; Aroca, Ricardo; Romano, Daniela (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book presents the advances in plant salinity stress and tolerance, including mechanistic insights revealed using powerful molecular tools and multi-omics and gene functions studied by genetic engineering and advanced biotechnological methods. Additionally, the use of plant growth-promoting rhizobacteria in the improvement of plant salinity tolerance and the underlying mechanisms and progress in breeding for salinity-tolerant rice are comprehensively discussed. Clearly, the published data have contributed to the significant progress in expanding our knowledge in the field of plant salinity stress and the results are valuable in developing salinity-stress-tolerant crops; in benefiting their quality and productivity; and eventually, in supporting the sustainability of the world food supply.